China's emerging hi-politics in East Asia - Karim, M.A. (2013)
Aim of this paper is to highlight the high-politics being practised by China in East Asia, ostensibly as a kind of fait accomplish, and upshot of national aspirations. This is almost an inexorable consequence mainly due to presence of issues that are likely to trigger conflict, may be even a limited war. Issues range from flash points to economic interdependence, and leadership. Hegemonic transition, replacing hegemonic stability, may be at work. The paper concludes with the likely ramifications that may spawn.